Geometric Formulas for Gusset Plate Design - Chambers, Janice J.; Bartley, Tony C. (Engineering Journal, 2007)
Common approaches to compute the yield and buckling resistances of gusset plates require knowledge of the lengths yc, ycf , yb, ybf, L1, L2, and L3, (Figures 2 and 7). While numerical values for these resistances have been presented in the literature, formulas for yc, ycf , yb, ybf, L1, L2, and L3 have not been published. This paper presents the derivation and validation of equations to compute these lengths. The equations are summarized in flow charts that can be incorporated into software for practical applications. The formulas provided for yc, ycf, yb, ybf, L1, L2, and L3 enable optimization of gusset plate design.